Histopathological Changes of Two Antigens Prepared from Methicillin-Resistant Staphylococcus aureus in Rats - Zainab Dakhil Degaim,; Wafaa Sadoon Shani,; Saad Salman Hamim, (University of Thi-Qar Journal of Science, 2020)
The aim of the present study was to determine the effect of two prepared antigens fromMethicillin-resistantStaphylococcus aureus (MRSA), whichincluded crude alpha toxin (Hla) and heat inactivate bacterial suspension (HIBS) in rats through the examination of the inflammatory response of both antigens on primary and secondary lymphoid organs (thymus gland and spleen), respectively. Examination of sections from spleen of rats treated with HIBS antigen induced high immune response compared with rats treated with Hla antigen which induce mild immune response by established changes. The histological observations on sections from thymus gland of rats treated with HIBS had the ability to induce different changes than Hla antigen compared with control group.